Pemberian Bantuan Konsultasi Hukum Secara Gratis oleh DPC PERADI Surabaya Bersama Pemerintah Kota Surabaya - Zahra Adelia (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The collaboration between DPC PERADI Surabaya and the Surabaya City Government in providing free legal assistance is an interesting example of synergy between the public and private sectors. This research analyzes the collaboration model that was built, the obstacles faced, and its impact on government governance and fulfilling the rights of underprivileged citizens. The research results show that this collaboration model is effective in increasing the efficiency and effectiveness of legal services. However, a stronger coordination mechanism is needed to ensure program sustainability.